PERPUSTAKAAN LAB - Anthony Christianto; Budi Adelar Sukada (Jurusan Arsitektur dan Perencanaan, 2019)
The millennial generation is a periodical generation that includes people who were born in the year 1980–2000 who have the will to improve oneself, to be acknowledged, do things instantly and have a deeper understanding about technology. This generation that is well known for pioneering in the field of technological development should be provided with a range of education, both independently or collaboratively, so as to support each individual in creating various innovation for a better future, thus achieving the real self-actualization. To support it, an open space should be available for the millennials to conduct experimental or social and contextual learning for understanding the technological knowledge better. According to the method of the developmental stages of building typology ranging from the prototypical to the stereotypical, the presence of lab-rary (lab library) hopes to give a solution for the millennials to be supplied with the sophisticated and comprehensive technological education, through hands-on experience via experimental laboratory, or a diverse range of theoritical book collection that is accompanied with discussion rooms throughout the plan to enhance the collaborative learning of technology and its advancements. Lab-rary hopes to provide the contemporaneity values for the millennial users that use it as a place to study, co-create, collaborate in a team or as a temporary playroom all built under one single roof that vows to create a living educational platform for the self-improvement of millennials. AbstrakGenerasi milenial merupakan sebuah jenjang generasi yang lahir pada tahun 1980–2000 yang memiliki keinginan untuk mengembangkan potensi diri, diakui, serba instan dan paham lebih dalam di bidang teknologi. Milenial yang seyogyanya merupakan pelopor dalam perkembangan berbasis teknologi wajib dibekali oleh pelbagai edukasi, baik secara mandiri maupun kolaboratif, dalam mendukung individu menciptakan berbagai inovasi untuk masa depan yang lebih baik, agar mencapai tingkat aktualisasi diri yang nyata. Untuk menunjang aktivitas tersebut, diperlukan wadah bagi para milenial dalam melakukan pembelajaran eksperimental maupun secara sosial dan kontekstual dalam mencari ilmu pengetahuan yang lebih dalam. Sesuai dengan metode tipologi perkembangan fungsionalitas perpustakaan dari prototipe hingga stereotipe, kehadiran perpustakaan lab diharapkan dapat menjadi salah satu solusi bagi para milenial untuk mendapatkan edukasi teknologi yang mutakhir dan komprehensif, baik secara pengalaman langsung melalui laboratorium-laboratorium praktik yang bersifat eksperimental, maupun melalui koleksi buku teoritikal yang diselingi dengan ruang-ruang diskusi untuk membuka wawasan yang lebih luas akan pengetahuan tentang teknologi. Perpustakaan lab diharapkan dapat menghadirkan nilai-nilai kesejamanan bagi para pengguna milenial yang menggunakan wadah tersebut untuk belajar, berkreasi, berkolaborasi secara kelompok dan mandiri atau sebagai tempat pelesiran sementara yang disatukan di dalam satu atap sebagai ruang edukatif untuk pengembangan diri generasi milenial.